EDUCATION AND TRAINING OF ENGLISH ACCOUNTANTS. - Murphy, Mary E. (The Accounting Review, 1938)
Abstract The problem in contemporary business education of determining the proper emphases of theory and of practice is admirably illustrated in the education of accountants in England. The few universities offering accounting courses, notably the University of London in its Department of Business Administration, stress the development of a general intellectual background which may be drawn upon when future problems are presented.' English business men as a whole do not believe that an academic training in theory is a substitute for practical business experience. They frequently contend that no phase of business can be learned without exposure, over a period of time, to practical situations. That this mind-set exists cannot be denied and anyone attempting to attack an educational problem in England, whether it concerns education for accountancy or for any other business profession, must at the start overcome the prejudice which lies deep in the mind of the older generation of business men in that country.